Marginalized centre: Wana people and the geography of power - Scalici, Giorgio (Journal of the British Association for the Study of Religions, 2019)
The Wana of Morowali (Indonesia) are nowadays a small endangered community marginalized by the Indonesian government, world religions and the other communities in the area but, according to their own mythology, they are not the periphery of the world, but the real centre of it. Their cosmogonic myth tells how the Wana land (Tana Taa) was the first land placed on the primordial waters and it was full of mythical power, a power that, when the land was spread around the world to create the continents, abandoned the Wana to donate wealth and power to the edge of the world: the West. This myth has a pivotal role in the Wana worldview, their categorization of the world and the power relationships in it. The Wana reverse the traditional relationship between centre and periphery, placing themselves in a powerless centre (the village or the Tana Taa) that gave all its power to a periphery (the jungle or the West) that must be explored to obtain power and knowledge. This relationship not only expresses a clear agency in shaping the relationship of power with forces way stronger than the Wana (Government and world religions) but also creates internal hierarchies based on the access to this knowledge; granted to men and partially precluded to women due to the cultural characterizations of these genders. Indeed, the majority of shamans, called tau walia (human-spirit), are men, and they are the only one that can travel between the human and the spiritual world, obtaining a spiritual and social power. In this article, we will see how Wana categorise the world and use religion, rituality and gender to express their agency to cope with the marginalization by the government, the world religions and the other community in the area.